Electrochemical Behavior of Chemical Conversion Coated Aluminum ASA6061 in Chromic Acid - S. Yaro, Aprael; Sh. Hussain, Muslet; H. Rashid, Khalid (Iraqi Journal of Chemical and Petroleum Engineering, 2007)
The corrosion behavior of bare and chemical conversion coated (through anodizing) aluminum ASA 606 I in stagnant chromic acid solutions . Solutions of 2, 6 & J O wt. % Cr03 at 45°C, have been investigated using polarization technique. The anodizing experiments were conducted under fixed conditions of 35 minute exposure time and 30 volt supplied voltage. The most important feature achieved was the great difference in behavior between the anodic polarization curves for bare and anodized aluminum in different concentrations of chromic acid solutions.